Profil Tekanan Darah pada Kelompok Usia Dewasa Muda di Lingkungan Kampus - Yadi Jayadilaga (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Reported that hypertension contributes to around 9.4 million deaths worldwide each year. This makes it one of the main risk factors for cardiovascular disease and related deaths. The prevalence of hypertension in individuals aged 18-39 years shows a figure of around 7.5%. At the global level, stroke, heart disease, and hypertension rank first, second, and twenty-ninth in causes of death. In Indonesia, the percentage of deaths from 50 diseases that cause death shows that stroke contributes 23.48%, heart disease 9.89%, and hypertension 3.02%. This study is a quantitative descriptive study with a cross-sectional approach that aims to describe the blood pressure profile in students. The population in this study were active students aged 18-23 years. The sampling technique used the purposive sampling method. The results showed that the average blood pressure in men tended to be higher than in women. Blood pressure in male students was an average of 128.9 / 83.25 mmHg and women 118.25 / 76 mmHg. The average blood pressure in men is included in the pre-hypertension category. Various factors cause hypertension at a young age, mainly caused by lifestyle, diet, smoking behavior and lack of physical activity. High blood pressure in young adults is strongly associated with an increased risk of heart and kidney disease later in life. Therefore, various forms of prevention are needed, especially related to behavioral changes so that complications do not occur in the future.